KM Implementation in Banking Sector: A Systematic Literature Review - Ridwan Marbanie; Faiz Rizqullah Pratama; Dana Indra Sensuse; Imairi Eitiveni; Deden Sumirat Hidayat (Green Publisher Indonesia, 2026)
This study aims to comprehensively understand the application of knowledge management (KM) in the financial sector through a systematic literature review (SLR) technique. We analyzed 46 papers systematically selected from various academic databases, representing various aspects of KM applicable to the financial sector, including implementation strategies, drivers, and barriers of implementation. Using the SLR approach, we identified, evaluated, and synthesized findings from the relevant literature to produce a clear picture of how KM is applied in organizations, particularly the finance and banking sector. This research delves deeply into how internal and external factors influence the success of KM implementation, including information technology, organizational culture, leadership, and regulation. From this analysis, we identified key strategies that can facilitate effective KM implementation in the financial sector, including IT capacity building, change management, and a strong internal communication strategy. The results suggest that KM plays a critical role in improving the performance, innovation, and sustainability of the financial sector through optimizing knowledge management and utilization. Moreover, a combination of adequate technological support, an organizational culture that supports knowledge sharing, and visionary leadership are key to overcoming barriers and maximizing KM success in the financial sector. This research provides valuable insights for stakeholders in the financial sector to design and implement effective KM strategies, while paving the way for further research on KM optimization in the face of dynamic financial sector challenges.